An analysis of Liberia's 2007 national health policy: lessons for health systems strengthening and chronic disease care in poor, post-conflict countries - Chan Brian T; Kruse Gina R; Lee Patrick T; Massaquoi Moses BF; Panjabi Rajesh R; Dahn Bernice T; Gwenigale Walter T (Globalization and Health, 2011)
Abstract Background Globally, chronic diseases are responsible for an enormous burden of deaths, disability, and economic loss, yet little is known about the optimal health sector response to chronic diseases in poor, post-conflict countries. Liberia's experience in strengthening health systems and health financing overall, and addressing HIV/AIDS and mental health in particular, provides a relevant case study for international stakeholders and policymakers in other poor, post-conflict countries seeking to understand and prioritize the global response to chronic diseases. Methods We conducted a historical review of Liberia's post-conflict policies and their impact on general economic and health indicators, as well as on health systems strengthening and chronic disease care and treatment. Key sources included primary documents from Liberia's Ministry of Health and Social Welfare, published and gray literature, and personal communications from key stakeholders engaged in Liberia's Health Sector Reform. In this case study, we examine the early reconstruction of Liberia's health care system from the end of conflict in 2003 to the present time, highlight challenges and lessons learned from this initial experience, and describe future directions for health systems strengthening and chronic disease care and treatment in Liberia. Results Six key lessons emerge from this analysis: (i) the 2007 National Health Policy's 'one size fits all' approach met aggregate planning targets but resulted in significant gaps and inefficiencies throughout the system; (ii) the innovative Health Sector Pool Fund proved to be an effective financing mechanism to recruit and align health actors with the 2007 National Health Policy; (iii) a substantial rural health delivery gap remains, but it could be bridged with a robust cadre of community health workers integrated into the primary health care system; (iv) effective strategies for HIV/AIDS care in other settings should be validated in Liberia and adapted for use in other chronic diseases; (v) mental health disorders are extremely prevalent in Liberia and should remain a top chronic disease priority; and (vi) better information systems and data management are needed at all levels of the health system. Conclusions The way forward for chronic diseases in Liberia will require an increased emphasis on quality over quantity, better data management to inform rational health sector planning, corrective mechanisms to more efficiently align health infrastructure and personnel with existing needs, and innovative methods to improve long-term retention in care and bridge the rural health delivery gap.